2014
DOI: 10.4168/aair.2014.6.3.242
|View full text |Cite
|
Sign up to set email alerts
|

Small Airway Impairment and Bronchial Hyperresponsiveness in Asthma Onset

Abstract: PurposeOur study tried to find a relationship between baseline FEF25-75% and airway hyperresponsiveness (AHR) and whether a greater FEF25-75% impairment may be a marker of a more severe hyperresponsiveness in subjects with normal FEV1 and FEV1/FVC and suggestive asthma symptoms. Besides, we tried to asses a FEF25-75% cut-off value to identify hyper-reactive subjects.Methods4,172 subjects (2,042 M; mean age: 38.3±14.9; mean FEV1 % predicted: 100.5±12.7 and FEV1/FVC: 85.4±6.8) were examined after performing a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…Compared to the CVID patients without BHR, those with BHR also displayed reduced values for FEV 1 (92 vs. 100%), FEV 1 /FVC (100 vs. 105%) and, interestingly, MEF25 (71.5 vs. 107.8%), implying the predominant impairment of the peripheral airways. This observation corresponds well with findings in pediatric patients with allergic rhinitis and at the time of asthma onset [37, 38]. We have thus confirmed that a decrease in MEF25 is associated with BHR, also in patients with underlying humoral immunodeficiency.…”
Section: Discussionsupporting
confidence: 77%
“…Compared to the CVID patients without BHR, those with BHR also displayed reduced values for FEV 1 (92 vs. 100%), FEV 1 /FVC (100 vs. 105%) and, interestingly, MEF25 (71.5 vs. 107.8%), implying the predominant impairment of the peripheral airways. This observation corresponds well with findings in pediatric patients with allergic rhinitis and at the time of asthma onset [37, 38]. We have thus confirmed that a decrease in MEF25 is associated with BHR, also in patients with underlying humoral immunodeficiency.…”
Section: Discussionsupporting
confidence: 77%
“…However FEF 25-75% measurements can vary markedly and change in proportion to the FVC. [22][23][24] In addition, abnormalities in mid-range flow measurements during forced exhalation are not specific for small airway disease in individual subjects. 25 Interestingly, all of the subjects with asthma (n ϭ 4, 6.3%) in this study, including 2 subjects with Churg-Strauss syndrome, exhibited a reduced FEF 25-75% .…”
Section: Discussionmentioning
confidence: 99%
“…Asthma patients with no symptoms, normal lung function, can also find obstruction in small airway. FEF 25-75 is generally considered as an approximate measure of the small airways caliber and thus its reduction represents a small airways obstruction caused by asthma inflammation (14). FEF 25-75 percent predicted should be evaluated in clinical studies of asthma in children and might be of use in predicting the presence of clinically relevant reversible airflow obstruction.…”
Section: Asthma In Childrenmentioning
confidence: 99%